Competence of Non-PLB Teachers’ Teams (Preparation and Performance Impact Assessment) - Desak Ketut Caturwangi; Budiyanto Budiyanto; Ari Wahyudi (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2017)
The efforts to improve competency of non-PLB (Special Education) SLB (Special School) teachers in Bali Province have been programmed by Disdikpora (Dinas Pendidikan Pemuda dan Olahraga/the Office of Youth and Sports) of Bali Province in the form of Training of Teachers’ Competency of SLB held in P4TK TK and PLB Bandung. This study was conducted to describe the efforts of the Officer of Youth and Sports of Bali Province in the preparation of the implementation of Training for Teachers’ Competency of SLB non-PLB in Denpasar, the conformity of training material and to determine the implications of SDLB non-PLB teachers’ performance in Denpasar in planning, implementing, and assessment of learning. This type of the research approach is descriptive qualitative. This research was conducted at the Officer of Education, Youth and Sports in Bali Province namely SLB A, B, C and C1 in Denpasar city. The data collection techniques used included observation, interview and documentation. The results of this study indicated that the competence increasing programs of non-PLB SDLB teachers in Denpasar accomplished through cooperation between Disdikpora of Bali province and P4TK TK and PLB Bandung. The Structural program supports SDLB teacher competence in teaching-learning process. Teachers of non-PLB SDLB can make a plan, implement and assess learning. Based on the above results, it can be concluded that: (1) program to improve the quality of SLB teachers in Bali province has been pursued through the implementation of SLB Teacher Competency Training. (2) The training materials is in accordance with the principles of ABK (Special need children) learning. (3) In the learning planning process, it is found some teachers who still need assistance processUpaya meningkatkan Kompetensi Guru SLB Non-PLB di Provinsi Bali telah diprogramkan oleh Dinas Pendidikan Pemuda dan Olahraga Provinsi Bali dalam bentuk Diklat Kompetensi Guru SLB yang dilaksanakan di P4TK TK dan PLB Bandung. Penelitian ini bertujuan untuk mendeskripsikan upaya Dinas Pendidikan Pemuda dan Olahraga Provinsi Bali dalam penyiapan pelaksanaan Diklat Kompetensi Guru SLB Non-PLB di Kota Denpasar, mendeskripsikan kesesuaiaan materi diklat dan untuk mengetahui implikasi kinerja guru SDLB Non-PLB Kota Denpasar dalam kegiatan perencanaan, pelaksanaan, dan penilaian pembelajaran. Pendekatan penelitian ini adalah kualitatif dengan jenis penelitian adalah deskriptif. Penelitian ini dilaksanakan di Dinas Pendidikan Pemuda dan Olahraga Provinsi Bali, SLB A, B, C dan C1 Kota Denpasar. Teknik pengumpulan data yang digunakan meliputi observasi, wawancara, dokumentasi. Hasil penelitian ini menunjukan bahwa program peningkatan kompetensi guru SDLB non-PLB di Kota Denpasar terlaksana melalui kerjasama antara Disdikpora Provinsi Bali dengan P4TK TK dan PLB Bandung. Struktur Program menunjang kompetensi guru SDLB dalam proses belajar-mengajar. Guru SDLB Non-PLB dapat merencanakan, melaksanakan dan menilai pembelajaran. Berdasarkan hasil penelitian di atas dapat disimpulkan bahwa; (1) program peningkatan kualitas guru SLB di Provinsi Bali telah diupayakan melalui pelaksanaan Diklat Kompetensi Guru SLB; (2) materi diklat sesuai prinsip-prinsip pembelajaran ABK.; (3) proses perencanaan pembelajaran, ditemukan beberapa orang guru yang masih membutuhkan proses pendampingan.DOI: http://dx.doi.org/10.17977/um029v4i12017p079